Cross-Talk Between Inflammation and Fibroblast Growth Factor 10 During Organogenesis and Pathogenesis: Lessons Learnt From the Lung and Other Organs - Marega, Manuela; Chen, Chengshui; Bellusci, Saverio (Frontiers in Cell and Developmental Biology, 2021)
The adult human lung is constantly exposed to irritants like particulate matters, toxic chemical compounds, and biological agents (bacteria and viruses) present in the external environment. Through the breathing process, these irritants travel through the bronchi and bronchioles to reach the deeper lung represented by the alveoli which constitute the minimal functional respiratory structure. The local biological responses that follow need to be tightly controlled in order to prevent a massive inflammatory response leading to loss of respiratory function. Cells, cytokines, chemokines and growth factors intervene collectively to re-establish tissue homeostasis, fight the aggression and replace the apoptotic/necrotic cells with healthy cells through proliferation and/or differentiation. Among the important growth factors at play during inflammation, members of the fibroblast growth factor (Fgf) family regulate the repair process. In particular, Fgf10 is known to be a key factor for organ morphogenesis and disease. Inflammation is influenced by Fgf10 but can also impact Fgf10 expression per se. Unfortunately, the connection between Fgf10 and inflammation in organogenesis and disease remains unclear. The aim of this review is to highlight the reported players between Fgf10 and inflammation and to propose new avenues of research in this important area.